IDENTIFIKASI KANDUNGAN TANNIN DAN SAPONIN HIJAUAN PAKAN KAMBING DI DESA TUANANGA KECAMATAN POTO TANO KABUPATEN SUMBAWA BARAT (SANGKAREANG, 2022)
This study aims to determine the levels of tannin and saponin compounds contained in Moringa leaves, bidara leaves and Javanese/jaranan leaves used as forage for goats in Tuananga Village, Poto Tano District, West Sumbawa Regency. The research method used is laboratory observation using Ultra Violet-Visible Spectroscopy (UV-VIS) Spectrophotometer at the Integrated Chemistry Laboratory, Faculty of Pharmacy, Stikes Bhakti Husada Mulia Madiun. The results showed that the tannin and saponin content quantitatively in the three types of goat forage, namely moringa leaf tannins 15.31%, bidara leaf 6.69% and Java/jaranan leaf 15.01%. The content of saponins in Moringa leaves is 13.10% in bidara leaves 20.10% and Java/jaranan leaves are 14.74%. Based on these data, it can be concluded that the tannin content of moringa leaves in this study was higher than that of bidara leaves and javan/jaranan leaves and saponins were higher in bidara leaves compared to moringa leaves and javan/jaranan leaves.